The role of serum IL-6 changes in evaluation of endometriosis - Hassan AL-Tai, Tharwa H.; AL-Hadithi, Hayfaa S.; Abdulsalam, Hind S. (Journal of the Faculty of Medicine Baghdad, 2013)
Background:- Endometriosis is a common chronic gynecological disorder characterized by the presence and proliferation of functional endometrial gland and stroma outside the uterine cavity, affecting approximately 10% of reproductive age women. Il-6 level increased in the patient with endometriosis.Objective:- Evaluate the correlation of IL-6 levels with the degree of severity of endometriosisPatients and methods:- In this study, 84 samples 51women with endometriosis (20 newly diagnosed and 31 treated cases) and 33 of healthy control group, were collected starting from November 2011 to end of January 2012, to investigate the IL-6 serum level by using ELISA kit.Results :- Endometriosis patients mainly presented at the age between (28-37). IL-6 serum levels were significantly decrease in those with stage IV endometriosis. Also appear to be significantly affected by the use of danazol or zoladex treatment of endometriosis and remain low even in treated patients. Serum IL-6 test was highly specific but with low sensitivity.Conclusion:-Serum IL-6 concentration seem to be the highly specific test that can be used as an early detection marker for endometriosis.